Toll-like receptor 4 deficiency in mice impairs venous thrombus resolution - Yuan, Haixin; Huang, Xiaoxi; Ding, Jie (Frontiers in Molecular Biosciences, 2023)
Toll-like receptor 4 (TLR4) is crucial to the development of sterile inflammatory responses. The dissolution of deep venous thrombosis (DVT) is similar to sterile inflammation, so we hypothesized that TLR4 was involved. We evaluated the effects of TLR4 deficiency on thrombus lysis in vivo, and explored the mechanisms in vitro. DVT mouse model was established by inferior vena cava (IVC) ligation. The TLR4-/- mice had significantly elevated weight/length ratios of thrombi at 3 and 7 d and increased collagen content at 3 d after IVC ligation, in addition to significantly lesser intrathrombus infiltration of neutrophils and macrophages, lower monocyte chemoattractant protein-1 (MCP-1) and matrix metalloproteinase-9 (MMP-9) expression in thrombus tissue sections and homogenates, and lower pro-MMP-9 activity at 3 d after IVC ligation than wild-type mice. In vitro, lipopolysaccharide (LPS) acted on wild-type peritoneal macrophages. It can activated TLR4/NF-κB signalling pathway in a concentration-dependent manner, initiated p65 nuclear translocation, IκBα phosphorylation and degradation, MMP-9 and MCP-1 transcription. However, in peritoneal macrophages lacking TLR4, similar effects were not seen. Taken together, TLR4 participates venous thrombus resolution and may have implications in DVT treatment.